An Overview of the Effectiveness of Entrepreneurship Education in Universities - Ilie Livia; Budac Camelia (Studies in Business and Economics)
To thrive in a rapidly changing and challenging economic environment, developing future-oriented and entrepreneurial skills is essential, both for enhancing employability of individuals and for driving economic growth in a society. Entrepreneurial education, as a key component of the third mission of universities, equips individuals with the creativity, resilience, and adaptability needed to innovate, lead, and contribute meaningfully to society. In the last decades, universities were challenged to design and implement effective entrepreneurship education programs that not only teach about entrepreneurship but foster an entrepreneurial mindset to their students in order to face more smoothly the labor market challenges and to allow them to remain competitive throught the entire career. This paper provides an overview of entrepreneurial education in universities and the key success factors identified that may conduct to effective entrepreneurship education programs that lead to entrepreneurial actions of learners.